2015
DOI: 10.5194/bg-12-177-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of soil moisture on de novo monoterpene emissions from European beech, Holm oak, Scots pine, and Norway spruce

Abstract: Abstract. Impacts of soil moisture on de novo monoterpene (MT) emissions from Holm oak, European beech, Scots pine, and Norway spruce were studied in laboratory experiments. The volumetric water content of the soil, , was used as the reference quantity to parameterize the dependency of MT emissions on soil moisture and to characterize the severity of the drought.When dropped from 0.4 m 3 × m −3 to ∼ 0.2 m 3 × m −3 slight increases of de novo MT emissions were observed but with further progressing drought the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…In addition, several studies have reported that isoprenoid emissions continue under drought when photosynthesis has already decreased substantially and even increases in isoprenoid emissions during the first stages of the drought stress can occur (e.g. Bertin & Staudt, ; Pegoraro et al ., ,b; Fortunati et al ., ; Genard‐Zielinski et al ., ; Potosnak et al ., ; Wu et al ., ). Similarly, our measurements show that isoprenoid emissions continued to increase concurrently with a decrease in photosynthetic CO 2 fixation at the beginning of the summer (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, several studies have reported that isoprenoid emissions continue under drought when photosynthesis has already decreased substantially and even increases in isoprenoid emissions during the first stages of the drought stress can occur (e.g. Bertin & Staudt, ; Pegoraro et al ., ,b; Fortunati et al ., ; Genard‐Zielinski et al ., ; Potosnak et al ., ; Wu et al ., ). Similarly, our measurements show that isoprenoid emissions continued to increase concurrently with a decrease in photosynthetic CO 2 fixation at the beginning of the summer (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…No significant interaction between O 3 and drought was found in leaf‐unit isoprene emission, suggesting that the stimulation due to a moderate drought did not significantly affect the negative response of isoprene to E‐O 3 and vice versa, thus confirming an uncoupling of A sat and isoprene emission under stress (Wu et al . ). When isoprene emission was up‐scaled to the plant level, however, WW plants emitted around twice isoprene in clean air relative to E‐O 3 .…”
Section: Discussionmentioning
confidence: 97%
“…; Wu et al . ). Therefore, studies on the combined effects of O 3 and drought on BVOC emissions are really needed in order to better understand how plants will react under future climatic and pollution scenarios.…”
Section: Introductionmentioning
confidence: 97%
“…These α-pinene fluxes values range from equivalent to six times higher than the default MEGAN estimates. These authors note that the highest values were associated with onset of drought in August, which may increase leaf temperatures due to reduced transpiration, resulting in increased terpene flux (Wu et al, 2015). Of these four studies, July rainfall was indeed the lowest (6.4 cm rainfall month − 1 vs. 9.1 to 19.6 cm rainfall month −1 for the other three studies).…”
Section: Monoterpenesmentioning
confidence: 90%